Evolving patient journey in the management of active perianal fistulizing Crohn's disease: A temporal perspective - Michiel T. J. Bak; Merel M. Verweij; Laurents P. S. Stassen; Christianne J. Buskens; Aagje M. Pronk; Jarmila D. W. van der Bilt; Liesbeth J. Munster; Nanne K. H. de Boer; Krisztina B. Gecse; Robert‐Jan B. Pierik; Caroline D. M. Witjes; Claire E. Fitzpatrick; et al. (Colorectal Disease, 2026)
Abstract Background Over recent decades, there has been a more pronounced shift towards earlier therapeutic intervention in luminal Crohn's disease (CD). However, it remains unclear if similar strategies apply to active perianal fistulizing CD (pCD). This study explores the patient journey by assessing pCD management across diagnostic time periods in a large national cohort. Methods Patients with active pCD were included in a multicentre cohort across 41 Dutch academic and non‐academic hospitals. Diagnostic modalities, medical and surgical treatments were evaluated over the pCD disease course, particularly within the first year after pCD diagnosis, and compared across four time periods: < 2010, 2010–2015, 2015–2020 and > 2020. Results Four hundred and forty patients were included (53.0% female; median pCD disease course 4.1 years). 12% were diagnosed before 2010, 11% in 2010–2015, 31% in 2015–2020, 46% after 2020. Over time, imaging (MRI or EUS) within the first year after pCD diagnosis was used in 37% of cases diagnosed before 2010 to 66%, 83% and 95% in subsequent periods. Endoscopic evaluation for proctitis was performed in 23%, 40%, 57% and 60%. First‐line anti‐TNF use was initiated in 27% followed by 58%, 68% and 69%. A seton was placed in 27% initially and in 42%, 51% and 52% in later years. Fistula surgery aimed at closure was performed in 14%, 4%, 8% and 19% over time. Conclusions This national cohort illustrates substantial progress in early pCD management over time. These shifts likely reflect growing clinical awareness of the importance of early and multidisciplinary interventions. However, surgical procedures aimed at fistula closure remain infrequently performed in the early disease course, which may be related to the inclusion of a predominantly therapy‐refractory patient group.